Reactions of laser-ablated aluminum atoms with nitrogen during condensation at 10 K. Infrared spectra and density functional calculations for Alx Ny molecular - Andrews, Lester; Zhou, Mingfei; Chertihin, George V.; Bare, William D.; Hannachi, Yacine (Физика низких температур, 2000)
Laser-ablated aluminum atoms react with dinitrogen on condensation at 10 K to form N₃ radicals and the subject molecules, which are identified by nitrogen isotopic substitution, further reactions on annealing, and comparison with isotopic frequencies computed by density functional theory. The major AlN₃ product is identified from three fundamentals and a statistically mixed nitrogen isotopic octet pattern. The aluminum-rich Al₂N and Al₃N species are major products produced on annealing to allow diffusion and further reaction of trapped species. This work provides the first experimental evidence for molecular AlxNy species that may be involved in ceramic film growth.